2022
DOI: 10.3390/v14030530
|View full text |Cite
|
Sign up to set email alerts
|

Escape and Over-Activation of Innate Immune Responses by SARS-CoV-2: Two Faces of a Coin

Abstract: In the past 20 years, coronaviruses (CoVs), including SARS-CoV-1, MERS-CoV, and SARS-CoV-2, have rapidly evolved and emerged in the human population. The innate immune system is the first line of defense against invading pathogens. Multiple host cellular receptors can trigger the innate immune system to eliminate invading pathogens. However, these CoVs have acquired strategies to evade innate immune responses by avoiding recognition by host sensors, leading to impaired interferon (IFN) production and antagoniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Several mechanisms may exist for apoptosis, decreased expression, and functional failure of immune cells. The decrease in T-cell numbers was negatively correlated with IL-6 and TNF-a levels (164), suggesting that increased inflammatory cytokines may promote T-cell failure and apoptosis. Moreover, the IL-2 signaling pathway is inhibited, negatively regulating CD8 + T cells (71) and inducing a decrease in lymphocytes.…”
Section: Lymphoid Tissue Damagementioning
confidence: 97%
“…Several mechanisms may exist for apoptosis, decreased expression, and functional failure of immune cells. The decrease in T-cell numbers was negatively correlated with IL-6 and TNF-a levels (164), suggesting that increased inflammatory cytokines may promote T-cell failure and apoptosis. Moreover, the IL-2 signaling pathway is inhibited, negatively regulating CD8 + T cells (71) and inducing a decrease in lymphocytes.…”
Section: Lymphoid Tissue Damagementioning
confidence: 97%
“…SARS-CoV-2 has strategies to avoid being detected or acted upon by the immune system. Several studies have together shown that the SARS-CoV-2 immune evasion strategy involves restricting the interferon (IFN) system, resulting in low type I and II IFN responses, as well as low IFN-stimulated genes (ISGs) during the early stages of COVID-19 [ 31 , 32 ]. The SARS-CoV-2 proteins responsible for this include non-structural protein 1 (NSP1), NSP8, NSP9, NSP13, NSP15, ORF9b, and ORF6 [ 33 , 34 , 35 ].…”
Section: Innate Immune Responsementioning
confidence: 99%
“…In response to infection, host cells mount antiviral responses. However, SARS-CoV-2, like many other viruses, has developed various strategies to escape cellular antiviral responses, similarly to Dengue, SARS-CoV-1, MERS-CoV (1). It is therefore important to elucidate the interactions of the SARS-CoV-2 with host proteins to gain better insights into virus infection and pathogenesis, and to potentially reveal novel options for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%